Monitoring the Adequacy of Catch-Up Growth Among Moderately Malnourished Children Receiving Home-Based Therapy Using Mid-Upper Arm Circumference in Southern Malawi - Connor, Nicholas E.; Manary, Mark J. (Maternal and child health journal, 2011)
Each year more children die from moderate than severe malnutrition. Home-based therapy (HBT) using Ready-to-Use Therapeutic Foods (RUTF) has proven to successfully treat uncomplicated childhood malnutrition on an outpatient basis. This study attempts to discern if Mid-upper Arm Circumference (MUAC) measurements collected by community-based health aides have the potential to monitor changes in nutritional status among moderately malnourished Malawian children while undergoing HBT using RUTF. Retrospective analysis was performed using the anthropometric data of 1,904 moderately malnourished children during treatment using RUTF. Changes in MUAC and changes in overall weight at 1 and 2 months of treatment were compared. Various geometric relationships were explored between the measures to find the most direct relationship. Models were developed to investigate anthropometric changes in children undergoing treatment. These data reveal that the correlation between the changes in MUAC and changes in weight over the course of treatment is statistically significant ( P < 0.0001). The relationship between a child’s change in MUAC and their change in weight is influenced by several cofactors related to their initial presentation. The power of change in weight to predict change in MUAC increases at the second month of treatment. Statistical modelling improves if children under the age of 12 months are omitted. Changes in MUAC reflect changes in overall body mass among moderately malnourished children undergoing HBT using RUTF suggesting that performance could possibly be monitored by village health aides in order to monitor a child’s performance on feeding programmes in low resource settings.